1983
DOI: 10.1152/ajpgi.1983.245.6.g780
|View full text |Cite
|
Sign up to set email alerts
|

Dantrolene and basal ileal sodium and chloride transport: involvement of calcium stores

Abstract: The effect of dantrolene on active ion transport in rabbit ileum was determined using the Ussing chamber short-circuiting technique. Dantrolene prevents the release of calcium from intracellular stores in skeletal muscle and was used to probe the role of intracellular calcium stores in intestinal ion transport. A saturated solution of dantrolene (approx 25 microM) decreased ileal short-circuit current and potential difference, increased conductance and mucosal-to-serosal and net Na and Cl fluxes, but did not a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1985
1985
1994
1994

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Its kinetic properties and sensitivity to vitamin D status are consistent with the conclusion that it represents a basal-lateral membrane-localized calcium pump. On the other hand, studies of neural and hormonal regulation of NaC1 absorption [8,9] lead to the conclusion that intestinal cells, like secretory epithelial cells [e.g., 30, 33] possess intracellular compartments which actively accumulate calcium. Since both endoplasmic reticulum and Golgi membranes may participate in calcium sequestration in exocrine acinar cells [20], it will be interesting to learn whether the ATP-dependent calcium transport activity measured in isolated basal-lateral membrane samples might actually be shared between the basal-lateral membrane population and previously unsuspected Golgi-and endoplasmic reticulum-derived populations.…”
Section: Discussionmentioning
confidence: 99%
“…Its kinetic properties and sensitivity to vitamin D status are consistent with the conclusion that it represents a basal-lateral membrane-localized calcium pump. On the other hand, studies of neural and hormonal regulation of NaC1 absorption [8,9] lead to the conclusion that intestinal cells, like secretory epithelial cells [e.g., 30, 33] possess intracellular compartments which actively accumulate calcium. Since both endoplasmic reticulum and Golgi membranes may participate in calcium sequestration in exocrine acinar cells [20], it will be interesting to learn whether the ATP-dependent calcium transport activity measured in isolated basal-lateral membrane samples might actually be shared between the basal-lateral membrane population and previously unsuspected Golgi-and endoplasmic reticulum-derived populations.…”
Section: Discussionmentioning
confidence: 99%
“…The stimulation of electrolyte absorption by dantrolene does not have immediate clinical implications for the therapy of diarrhoea. It is not known whether dantrolene has similar effects under in vivo conditions [2]. Moreover, as an agent that stimulates Na ÷ and C1-absorption by affecting intracellular calcium stores, dantrolene appears to have al- Table 1 Effect of dantrolene on unidirectional fluxes of Na ÷ and C1-in the small intestine of control and G. lamblia-infected animals Group/fluxes Control (U equiv, cm 2 h I) Experimental (U equiv, cm 2 h-1 ) Values are expressed as mean + SE of six determinations.…”
Section: Resultsmentioning
confidence: 99%
“…The role of intracellular calcium stores in the * Corresponding author. regulation of ion transport is probed by the use of dantrolene, a drug used clinically as a skeletal muscle relaxant that has been shown to trap calcium in intracellular stores in skeletal muscle [2]. A wide variety of hormones and neurotransmitters have been shown to cause cellular Ca 2+ mobilisation for the expression of an appropriate biological response.…”
Section: Introductionmentioning
confidence: 99%
“…Zimmer man et al [21] have shown a Ca2+ require ment for the effects of theophylline in the rat colon. Donowitz et al [7] have provided evi dence from studies with dantrolene that in tracellular Ca2+ stores can have a regulatoryrole in basal ion transport in the ileum. It is possible that these intracellular stores could also be involved in the secretory responses observed after addition of A23187 or the secretory detergents which possess similar ionophore activity [17,18].…”
Section: Discussionmentioning
confidence: 99%